Technical challenges in the application of adaptive management - Williams, Byron K.; Brown, Eleanor D. (Biological Conservation, 2016)
Adaptive management is an approach for simultaneously managing and learning about natural resources, by acknowledging uncertainty and seeking to reduce it through the process of management itself. Adaptive decision making can be applied to pressing issues in conservation biology such as species reintroduction, disease and invasive species control, and habitat restoration, as well as to management of natural resources in general. After briefly outlining a framework and process for adaptive management, we focus on an overview of the key technical issues related to problem framing and the ability of resource managers to learn from their experience. These technical issues include the treatment of uncertainty and its propagation over time; nonstationarity in long-term environmental trends; the applicability of adaptive management across scales; requirements for models and management alternatives that promote learning; the value of the information produced with adaptive management; the challenge to management of uncertainty and surprise; and institutional (social) learning. To accommodate these and other challenges that are now coming into focus, the learning-based approach of adaptive management will need to be adjusted and expanded in the future.
Keywords: Adaptive Management; Learning; Nonstationarity; Resilience; Uncertainty; Value of information

The Science in Adaptive Management - Ripley, Matt; Jaccard, Sabine (ILO, 2016)
‘Adaptive management’ is all the rage in international development circles. But to avoid yet another buzzword – we need to learn from the experience of natural resource science.
Keywords: IMPORTANT

Built to improve: Leveraging realtime M&E for adaptive youth employment programming - Skelton, John (Mercy Corps, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

All about behaviour: KAPE, Adaptation and ' Sticky' Institutional Change - Power, Greg (Global Partners Governance, 2016)
This paper describes Global Partners Governance’s (GPG’s) approach to institutional reform and political change. Developed over the last decade of working in some of the most complex and sensitive political environments with politicians and officials in parliaments, political parties, ministries and local government, it describes the KAPE® (knowledge-application-practice-effect) methodology that we adopt to get ‘sticky’ institutional and behavioural change. Contents 1) Two dimensions of ‘adaptive programmes’: Flexible delivery and getting behaviour change 2) Enabling Change: KAPE and The Logic of Institutional Reform (Knowledge-Application-Practice-Effect) - K: Knowledge – Defining the problem and what to do about it - A: Application – Making Systems Work in Practice - P: Practice – Pockets of good practice and establishing ‘the new normal’ - E: Effect – Improved performance and the ‘Ripple Effect’ 3) Measuring Impact: Monitoring and Evolving 4) Conclusion: Behavioural insights, adaptive management and sticky change

Towards an Alternative Development Management Paradigm? - Shutt, Cathy (Expertgruppen för biståndsanalys (EBA), 2016)
Demonstrating results has been a concern in international development cooperation ever since it was started and in recent years there has been an increased focus on achieving and reporting on “results”. Despite the fact that everyone involved in development cooperation wants to make a difference there has been a growing criticism from practitioners about the “results agenda” based on a concern that the approaches used are not fit for purpose. In the EBA-report, Cathy Shutt, at the University of Sussex, scrutinizes the recent critical debate about results based management, and the main arguments and motives behind the criticism. She shows that the debate is not only a matter of obsessive measurement and reporting of meaningless numbers for political accountability, but also a matter of problematic assumptions and how we think about development, evidence and learning. In the report, Shutt also explores what could be learned from those who are not just critiquing results based management approaches but also proposing alternatives. Are these new alternatives an answer to the criticism?
Keywords: IMPORTANT

Using adaptive development to support feminist action - O’Neil, Tam (ODI, 2016)
This paper looks at how adaptive development is being applied by gender programmes and argues that gender and adaptive development communities have much to offer each other.

Politics matters, so what? Time for bigger bets (and more learning) on adaptive programming - Alan (www.globalintegrity.org, 2016)
By Alan Hudson, Executive Director, Global Integrity, July 26, 2016 Politics matters. Context too. And blueprints have limited value. Our strategy is based on these insights, so we’re totally on board. A World Development Report (WDR) that puts power and politics...

Adapting Aid: Lessons from six case studies - Algoso, Dave; Beloe, Jon; Hemberger, Alison; Hill, Philippa; Proud, Emma (MercyCorps & IRC, 2016)
Keywords: IMPORTANT

When theory meets reality: assumptions, feasibility and implications of a complexity-informed approach - Buffardi, Anne (Methods Lab, 2016)
Over the last half century, repeated calls for adaptive learning in development suggests two things: many practitioners are working in complex situations that may benefit from flexible approaches, and such approaches can be difficult to apply in practice. • Complexity thinking can offer useful recommendations on how to take advantage of distributed capacities, joint interpretation of problems and learning through experimentation in complex development programmes. • However, these recommendations rely on underlying assumptions about relationships, power and flexibility that may not hold true in practice, particularly for programmes operating in a risk averse, results-driven environment. • This paper poses guiding questions to assess the fit and feasibility of integrating complexity informed practices into development programmes.

Balancing Inclusiveness, Rigour and Feasibility: Insights from Participatory Impact Evaluations in Ghana and Vietnam - van Hemelrijck, Adinda; Guijt, Irene (CDI, 2016)
This paper by Adinda Van Hemelrijck and Irene Guijt explores how impact evaluation can live up to standards broader than statistical rigour in ways that address challenges of complexity and enable stakeholders to engage meaningfully. A Participatory Impact Assessment and Learning Approach (PIALA) was piloted to assess and debate the impacts on rural poverty of two government programmes in Vietnam and Ghana funded by the International Fund for Agricultural Development (IFAD). We discuss the trade-offs between rigour, inclusiveness and feasibility encountered in these two pilots. Trade-offs occur in every impact evaluation aiming for more than reductionist rigour, but the pilots suggest that they can be reduced by building sufficient research and learning capacity.

Innovation for International Development: Navigating the Paths and Pitfalls - Ramalingam, Ben; Bound, Kirsten (NESTA, 2016)
Experiences, insights and practical advice from over 20 leading practitioners in innovation for international development, brought together in one collection.

Experiential Learning: Fostering lasting behavioural change - Norton, Brittney M. (Mercy Corps, 2016)
The term ‘experiential learning’ is often mistakenly used to describe any learning experience that involves participatory activities. This paper presents an overview of what true experiential learning is and how this form of learning allows for real-world application - thus promoting lasting behavioural change. Furthermore, it explains how experiential learning was adopted as the methodological core of the Prospects psychosocial programme in Liberia, which builds ‘pre-employment skills’ in 3,500 vulnerable youth aged 15-24 years. The goal of the paper is to provide other youth and education development practitioners with a resource that can be used to strengthen youth and behaviour change programmes through the incorporation of the experiential learning theory. In addition, this paper explains its application in the Prospects programme, before concluding with key considerations of such a design. 1

Clearing the fog: new tools for improving the credibility of impact claims - Befani, Barbara; D'Errico, Stefano; Booker, Francesca; Giuliani, Alessandra (iied Briefing Papers, 2016)
Development actors facing pressure to provide more rigorous assessments of their impact on policy and practice need new methods to deliver them. There is now a broad consensus that the traditional counterfactual analysis leading to the assessment of the net effect of an intervention is incapable of capturing the complexity of factors at play in any particular policy change. We suggest that evaluations focus instead on establishing whether a clearly-defined process of change has taken place, and improve the validity and credibility of qualitative impact statements. IIED research in Uganda shows that the methods of process tracing and Bayesian updating facilitate a dialogue between theory and evidence that allows us to assess our degree of confidence in ‘contribution claims’ in a transparent and replicable way.

Doing Development Differently at the World Bank: updating the plumbing to fit the architecture - Bain, Katherine A.; Booth, David; Wild, Leni (ODI, 2016)
Keywords: IMPORTANT